Democracy promotion in EU enlargement negotiations: more interaction, less hierarchy. Issue 5 (4th July 2019) - Grimm, Sonja
ABSTRACT: In the integration literature, the relationship of the European Union (EU) as a donor and the (potential) candidates for EU membership as recipients of democracy promotion is described as asymmetrical. The donor is portrayed to have full whereas recipients have moderate or even no leverage over democratic reform what brings a hierarchical notion of active donors versus passive recipients into the analysis. Taking the local turn into consideration, however, this contribution argues that democracy promotion, is better conceptualized as a dynamic interplay between external and domestic actors. It reveals the toolbox of instruments that both sides dispose of, traces the dynamic use of these instruments, and systematizes the structural and behavioural factors that constrain the negotiation interplay. A case study of negotiations over public administration reform in Croatia in the context of EU enlargement shows that domestic actors dispose of leverage that counterweights external leverage and mitigates the implied hierarchy.